A new species of Tetragonopterus Cuvier, 1816 (Characiformes: Characidae: Tetragonopterinae) from the rio Jari, Amapá, northern Brazil - Melo, Bruno F [UNESP]; Benine, Ricardo C [UNESP]; Mariguela, Tatiane C [UNESP]; Oliveira, Claudio [UNESP] (Sociedade Brasileira de Ictiologia, 2011)
Uma espécie nova de Tetragonopterus é descrita do rio Jari, um tributário da margem esquerda do rio Amazonas, na divisa entre os Estados do Amapá e Pará, norte do Brasil. Esta é morfologicamente diferenciada das outras espécies do gênero (T. argenteus, T. chalceus e T. rarus combinação nova) pelo formato losangular da mancha no pedúnculo caudal contra uma mancha arredondada a quadrangular nas demais espécies. Sequências parciais do gene mitocondrial citocromo oxidase C subunidade I de representantes de todas as espécies válidas de Tetragonopterus, incluindo esta espécie nova, foram analisadas. Os resultados obtidos revelaram uma significante distância genética entre esta espécie nova e as demais do gênero. É apresentada uma discussão sobre a nova combinação, Tetragonopterus rarus.

A new species of Tetragonopterus is described from the rio Jari, a tributary to the left margin of rio Amazonas, at the border between Amapá and Pará States, northern Brazil. It is morphologically diagnosed from the other species of the genus (T. argenteus, T. chalceus, and T. rarus new combination) by the lozenge-shaped spot on the caudal peduncle vs. rounded to square spot on the other species. Partial sequences of the mitochondrial gene Cytochrome Oxidase C subunit I, from representatives of all valid species of Tetragonopterus, including this new species, were analyzed. The obtained results revealed a significant genetic distance between the new species and its congeners. A discussion on the new combination, Tetragonopterus rarus, is also provided.
Keywords: COI gene; Genetic distance; Mitochondrial DNA; Neotropical fish; Taxonomy